Contributions to the Diatom Flora of the Aegean Sea and the Mediterranean Sea from the Turkish Coasts with Remarks on Rare Taxa - KALELI, AYDIN (Mediterranean Marine Science, 2022)
This study reports on newly recorded and several rare marine benthic diatoms from the Turkish coasts of the Aegean Sea. Altogether 510 species were observed from 6 locations throughout the Aegean Sea, and taxonomic and biogeographic remarks concerning thirty-four new recorded species are presented. Amongst the represented taxa, Amicula, Auricula, Cyclophora, Minidiscus, Oestrupia and Ralfsiella were observed for the first time in Turkish coastal waters. Biddulphia seychellensis, Cyclophora tabellariformis, Grammatophora maxima, G. gibberula, Amphicocconeis mascarenica, Cocconeis maxima, Amicula specululum, Caloneis egena, Diploneis dalmatica, D. droopii, Mastogloia affinis, M. linearis, M. mauritana and Oestrupia powelii var. vidovichii, which were rarely recorded from the coasts of the oceans and the Mediterranean Sea, were examined by light microscopy (LM) and scanning electron microscopy (SEM). Also, the findings revealed that the geographic range of A. mascarenica, B. seychellensis, C. tabellariformis and Psammodictyon corpulentum, which were distributed in warmer marine waters, has expanded to the temperate waters of the Aegean Sea. Additionally, the recently described species Hyalosira septata, from the loggerhead sea turtle carapace and the Turkish Mediterranean Sea coast was observed in the Aegean Sea. This study contributes to the diatom knowledge of marine waters from the understudied Aegean Sea coasts of Türkiye, enhancing the biogeography of some rare and well-established taxa.